IMPLEMENTASI SASARAN KESELAMATAN PASIEN PADA RUMAH SAKIT SWASTA DAN PEMERINTAH TERAKREDITASI PARIPURNA DI JAWA TIMUR - Cahyani, Faridha; Dewi, Arlina (Poltekkes Kemenkes Bandung, 2025)
Patient safety is an important factor in improving health services quality. Hospital accreditation aims to ensure patient safety by ensuring hospitals comply with established standards. Despite achieving Paripurna accreditation, hospitals still receive recommendations (accreditation surveyor findings) that must be followed up. The study aimed to evaluate whether there are differences in the fulfillment of Patient Safety Goals (SKP) standards in Paripurna-accredited private and government hospitals. This study is useful for improving service quality, especially patient safety aspects. The study result are expected to support the development of effective policies, hospital guidance, and priority strategies establishment in improving hospital quality. The study was conducted in February 2024 using descriptive and comparative quantitative methods. The research sample was 126 Paripurna-accredited hospitals in East Java. Data analysis used Tableau and the Mann-Whitney U statistical test. The results showed that both private and government hospitals had the most accreditation surveyor findings in standard SKP6 (reducing the risk of patient injury due to falls in outpatient unit), 33.91% and 25.64%, respectively. Government hospitals had the same number of accreditation surveyor findings in standards SKP6 and SKP2 (effective communication) at 25.64%. The p-value of 0.015 indicates that there was a statistically significant difference in the fulfillment of SKP standards between private and government hospitals. The study concluded that the SKP needs to be improved by planning strategic improvements to the assessment elements that received accreditation surveyor findings. Private hospitals need to take strategic steps through strict supervision of health workers' compliance with procedures and standards